Beyond Screens and Streams: Reimagining EdTech Pedagogy through Social Media Synergy-A Study with Special Reference to Selected Edtech Companies - M. Sakthivadivel; S. Ayyappan; Mayan.K.Sreerudran; Sharfunisa.N (International Journal of Engineering and Management Research, 2025)
Educational technology (EdTech) platforms increasingly depend on social media to attract learners, build trust and gather feedback. This study examines how social‑media factors including design, trust, targeting and challenges affect the operational performance and societal impact of EdTech companies. We propose a hybrid structural equation model (SEM) where social‑media design quality, perceived trust and targeting accuracy directly influence awareness and EdTech operations and indirectly affect the overall impact through intermediate constructs such as emerging reality and EdTech operations. Data for the model were collected through a survey of employees at EdTech firms; PLS‑SEM analysis confirmed strong relationships between social‑media marketing (SMM) and consumer brand engagement, which in turn influenced purchase intention. The model also identifies challenges such as platform algorithms, budget constraints and content overload—as barriers that feed back into operations.Research motivations stem from recent findings: group‑based social‑media interventions improved learning gains during the pandemic yet digital inequalities persist and access alone does not ensure equity. Additionally, EdTech firms face rising competition and must align marketing strategies with user engagement. Our SEM illustrates that high‑quality content and meaningful interaction strengthen emotional connections and brand engagement, thereby enhancing user satisfaction and operational effectiveness. Compared with traditional digital marketing, the proposed model integrates makespan and resource allocation concepts from manufacturing scheduling into the scheduling of social‑media campaigns, seeking to balance responsiveness (through shorter decision cycles) with resource utilisation (e.g., content creation, analytics). By mapping multi‑directional effects among constructs—design, trust, targeting, challenges, awareness, emerging reality, EdTech operations and impact—our model highlights how EdTech companies can strategically deploy social media to achieve both efficiency and equitable reach. The findings contribute to the growing literature on digital learning and provide practical guidance for EdTech managers aiming to optimise social‑media strategies and operations.